Persistent Laparoscopic Port-site Discharging Sinus: A Rare Case of Mycobacterium senegalense Infection - Vettakkara Kandy Muhammed Niyas; Vishakh C Keri; Binit Kumar Singh; Prabhat Kumar (International Journal of Mycobacteriology, 2020)
Laparoscopic port-site infections, though infrequent, undermine the advantages provided by minimally invasive surgeries. Persistent nonhealing discharging sinuses, not responding to conventional antibiotic therapy, pose diagnostic and therapeutic challenges. Sizeable number of these infections is caused by rapidly growing nontuberculous mycobacteria (NTM), and diagnosing these requires a high index of suspicion. We present a case of a nonhealing laparoscopic cholecystectomy umbilical port-site infection caused by Mycobacterium senegalense, a rare NTM. The patient recovered completely after 6 months of combination therapy with clarithromycin, trimethoprim-sulfamethoxazole, and levofloxacin.